Factors affecting raw milk quality in dairy value chain in Rajasthan (India): A comprehensive study - SINGH, VIKRAM; GUPTA, JANCY (The Indian Journal of Animal Sciences, 2016)
This paper outlines the quality of raw milk in the dairy value chain of Rajasthan and brings out the various factors and their association with raw milk quality. Four milk unions viz. Alwar, Bhilwara, Bikaner and Hanumangarh of Rajasthan Cooperative Dairy Federation (RCDF) were selected purposively. A list of dairy farmers of each DCS (Dairy Co-operative Society) was prepared, and 120 farmers were selected on the basis of proportionate random sampling. To analyze the factor affecting raw milk quality, milk samples were collected from three levels viz. pail, DCS and dock. The raw milk quality in the milk shed area of RCDF was affected by socio-economic factors, viz. social participation, education, experience in dairying and milk sale. Path analysis revealed various factors having substantial direct effect on milk quality at pail, DCS and at dock level.The impact of clean milk production (CMP) programme on the milk quality was positive at all the levels of dairy value chain.